Pengalaman Pasien Sindrom Koroner Akut yang Menjalani Kateterisasi Jantung di Rumah Sakit Panti Rapih Yogyakarta - Widyastanti, Christina Restu; Marti, Eva; Setya Widyastuti, Chatarina (STIKes Panti Rapih, 2024)
Background: Acute Coronary Syndrome (ACS) causes high mortality and increases every year, due to an imbalance between oxygen demand in the heart and blood flow due to the narrowing of the heart's blood vessels. The cardiac catheterization procedure can cause several responses in the patient, such as anxiety, pain, fear about the procedure, and fear of death, and this action is performed on the patient while conscious. so that patients can see directly the process of cardiac catheterization. After the procedure, the patient will be taken to the ICCU room for further post-catheterization care Objective: To find out the experiences of ACS patients undergoing cardiac catheterization at Panti Rapih Hospital, Yogyakarta. Methods: The research design used is qualitative with a descriptive phenomenology approach. The sampling technique was non-probability sampling (purposive sampling), with inclusion criteria for participants undergoing cardiac catheterization for the first time and having a stent/ring placed. The sample in this study was 5 participants according to data saturation, data collection used in-depth interviews with interview guidelines and tape recorders. The data analysis method used is from Creswell. Results: The study found six themes, namely 1) Internal and external motivation in performing cardiac catheterization 2) Surrender in undergoing cardiac catheterization, 3) The description of cardiac catheterization is not scary 4) Feelings of discomfort after cardiac catheterization 5) Positive feelings of after undergoing catheterization heart 6) Good service by health workers. The role of the nurse is very important in accompanying patients undergoing cardiac catheterization before, during, and after the procedure, because it will have an impact on the patient's psychology. For health workers, to provide services holistically, especially paying attention to psychological aspects such as providing support and explanations about cardiac catheterization procedures so as to reduce anxiety and provide patient satisfaction Keywords: Experience, Acute Coronary Syndrome, Cardiac Catheterization